40th International Conference on Organizational Science Development Values Competencies and Changes in Organizations 2021
DOI: 10.18690/978-961-286-442-2.4
|View full text |Cite
|
Sign up to set email alerts
|

Digitalni dvojčki v ergonomskih ureditvah delovnih mest

Abstract: t The approach to designing assembly lines and jobs in the modern world of Industry 4.0 is still too spontaneous. If we want to create a user-friendly workplace, it is necessary to include a myriad of variables with all the ergonomic principles. It is necessary to get involved in the process of progressive and holistic job design already in the phase of product design and the process of production and job design. Inadequate job planning can cause downtime in workflow engineering. If we want to be more efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Any workplace design should follow the principles of modern ergonomics. 46 We found that teachers are unaware of the consequences of sitting for long periods. In the Faculty of Health Sciences, 35% of the teaching staff have acquired knowledge about ergonomics during their training.…”
Section: Discussionmentioning
confidence: 85%
“…Any workplace design should follow the principles of modern ergonomics. 46 We found that teachers are unaware of the consequences of sitting for long periods. In the Faculty of Health Sciences, 35% of the teaching staff have acquired knowledge about ergonomics during their training.…”
Section: Discussionmentioning
confidence: 85%